2016
DOI: 10.1080/09593330.2016.1244568
|View full text |Cite
|
Sign up to set email alerts
|

Passive bioremediation technology incorporating lignocellulosic spent mushroom compost and limestone for metal- and sulfate-rich acid mine drainage

Abstract: Passive bioremediation of metal- and sulfate-containing acid mine drainage (AMD) has been investigated in a batch study. Multiple substrates were used in the AMD remediation using spent mushroom compost (SMC), limestone, activated sludge (AS), and woodchips (WC) under anoxic conditions suitable for bacterial sulfate reduction (BSR). Limestones used were of crushed limestone (CLS) and uncrushed limestone, provided at two different ratios in mixed substrates treatment and varied by the proportion of SMC and lime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Applications of SMC as biosorbent to remove heavy metals are presented in Table 6 . Generally, SMC has shown great adsorption capacity in removing single and multiple metal ions and is an excellent biosorbent as it minimizes the plugging in bioreactors and has large pore spaces and small void volume (Muhammad et al 2017 ). On the other hand, SMC contains different types of polymers such as lignin, cellulose and hemicellulos which are degraded into numerous pores that are suitable for metal adsorption (Kulshreshtha 2019 ).…”
Section: Converting Biosorbents To Biochar For Heavy Metals Removalmentioning
confidence: 99%
See 1 more Smart Citation
“…Applications of SMC as biosorbent to remove heavy metals are presented in Table 6 . Generally, SMC has shown great adsorption capacity in removing single and multiple metal ions and is an excellent biosorbent as it minimizes the plugging in bioreactors and has large pore spaces and small void volume (Muhammad et al 2017 ). On the other hand, SMC contains different types of polymers such as lignin, cellulose and hemicellulos which are degraded into numerous pores that are suitable for metal adsorption (Kulshreshtha 2019 ).…”
Section: Converting Biosorbents To Biochar For Heavy Metals Removalmentioning
confidence: 99%
“…Samsuri et al ( 2014 ) found that low pH creates higher hydrogen ion condition which competes with heavy metals for the sorption sites. High pH adsorbent can also act as alkalinity generator to increase the acidic pH in acid mine drainage, which subsequently facilitates the condition for metal removal (Muhammad et al 2017 ). Hence, by an increase in pH, more adsorption sites are available for heavy metals.…”
Section: Converting Biosorbents To Biochar For Heavy Metals Removalmentioning
confidence: 99%
“…Passive bioremediation technology incorporating lignocellulosic spent mushroom compost and limestone was used to treat metal-and sulfate-rich AMD (Muhammad et al, 2017). The spent mushroom compost greatly assisted the removals of sulfate and metals and also acted as an essential carbon source for BSR.…”
Section: Impacts Of Detrital Nano-and Micro-scale Particlesmentioning
confidence: 99%
“…Calcium carbonate usage for environment remediation is considered with growing interest, as CaCO 3 is quite biocompatible, and hence it does not pose a threat to any species [3]; CaCO 3 -based materials can in fact be employed for removal of both heavy metals or organic pollutants [4,5]. For this purpose, CaCO 3 can also be used in a composite with other materials [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%